O DISCURSO DE EDIR MACEDO NO LIVRO ORIXÁS, CABOCLOS E GUIAS. DEUSES OU DEMÔNIOS?: IMPACTOS E IMPASSES NO CENÁRIO RELIGIOSO BRASILEIRO - Santos, Valdelice Conceição dos (2010)
This thesis is a discourse analysis of the book Edir Macedo Orixás, Caboclos e Guias. Deuses ou Demônios? Our study is the discourse and rhetoric that M and the Universal Church of the Kingdom of God used to talk about the african-Brazilian religions and mediums in this book.We chose this book as an object of study because of the constant presence of this theme in the discourse and practices of the Universal Church, the success of the publication, with over four million copies sold, according to the controversy caused by the discourse of religion demonized african-brazilian and abilities. We tried to analyze the speech of Macedo and his Church the light of the impacts and predicaments caused by them in the religious landscape of Brazil. We list the discourse and rhetoric of to success and the creation of an identity of his Church. Our study differs from other investigations already published relating to the creation of religious identity and the use of accusatory mechanisms as an effective tool to convince and convey ideologies that promote the expansion of the Universal Church. We seek to bring to the academic discussion that the analysis of discourse of a religious literature can be a reference to study a religious institution, its mechanisms of identity, legitimacy and development in the religious landscape.(AU)